75 year anniversary of E. I. Schwartz - S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
This article is devoted to the 75 year anniversary of MD, professor, Eugene Schwartz. It represents the steps of his life and work, his scientific achievements. It shows the role of E. I. Schwartz in the development of molecular-genetic methods and their introduction into medical practice as well as his contribution to such field as molecular medicine.